MENINGKATKAN MOTIVASI BELAJAR MAHASISWA SEMESTER GANJIL MENGGUNAKAN METODE TANYA JAWAB PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS KARIMUN - Edi Kurniawan; Alpino Susanto; Muhiri; Fadli Surahman; Hilda oktri yeni; Sabrina Aisaputri (JURNAL MINDA, 2021)
This study aims to increase the learning motivation of odd semester students using the question and answer method in Islamic religious education courses at Karimun University and to increase the motivation of lecturers in research and the tridharma of higher education. The research method used in this research is Classroom Action Research. This research is designed for 3 (three) cycles and is collaborated with the Blended Learning Model by Norman Vaughan. The results of the first cycle of research the average value of students was 73.74 Students who completed 14 students (40.00%). Actions in the second cycle of student learning outcomes 74.42 reached 20 students who completed students (75.00%). The third cycle of student learning outcomes with an average of 78.57 students who completed 35 students (100.%). Thus, the application of the question and answer method in PAI learning can increase student learning motivation beyond the specified completeness criteria, namely 75.